Um estudo sobre a renda bruta de estabelecimentos rurais familiares de municípios da região Nova Alta Paulista, Estado de São Paulo, Brasil - Pinto, Leonardo de Barros [UNESP]; de Oliveira, Sandra Cristina [UNESP]; Higuchi, Mauricio Endo [UNESP]; Muchiuti, Julianna Coracini [UNESP]; dos Santos, Gabriela Dezan [UNESP]; Bianchi, Vinícius Rafael [UNESP] (My University, 2016)
Sustainable development, generation of employment and income, food security and regional development, along with the search for efficiency, represent strong influence against the growing importance of family farming. In this context, there is the emergence of new exploration strategies and the development of new management models of family farms. The aim of this work was to examine the different ways of generating income of family farms in three municipalities of the New Alta Paulista Region, which is situated at São Paulo state, Brazil, from the characteristics of those farms and the participation of farm and non-farm activities on family production systems. As a methodological analysis, was used multiple linear regression considering several explicative variables for the response variable, total gross income (TGI). The study showed that the variables a) ratio of farm income and TGI, b) total area of the farm, c) ratio of income earned through retirement and, or, pension and TGI, d) ratio of total number of animals and area of the farm, and, e) diversification index were considered the most significant variables (at significance level of 5%) for explaining the TGI.
A study on the gross income of family farms in municipalities of New Alta Paulista Region, State of São Paulo, Brazil
Keywords: Family farming; Farm and non-farm incomes; Pluriactivity; Statistical analysis